Effect of Restricted Group Sandplay on Interpersonal Sensitivity in College Students - Yu, Shuhan; Zhan, Liyu (Frontiers in Psychology, 2021)
Purpose: This study aims to investigate the intervention effect of group sandplay on the interpersonal sensitivity of college students and analyze the relationship between the theme and interactive behavior characteristics and the intervention effect of group sandplay especially during the period of COVID-19. Methods: Sixty college students were randomly assigned to the experimental group and the control group and subjected to three weeks of group sandplay and neutral task interventions, respectively. The interpersonal sensitivity subscale of the Symptom Checklist 90 (SCL-90) Scale was used to rate the interpersonal sensitivity of the two groups before and after the intervention. Self-compiled group sandplay interaction behavior coding and theme coding were used to analyze the groups’ sandplay characteristics before and after the intervention. Results: The interpersonal sensitivity level of the experimental group was significantly lower than that of the control group. The interpersonal sensitivity level of the experimental group after the sandplay intervention was significantly lower than that before the intervention, while the control group did not exhibit this difference. For the experimental group, the variation in the interpersonal sensitivity level was significantly negatively correlated with the change in warm, supportive behavior during group sandplay interaction. Conclusions: Group sandplay is effective in improving the interpersonal sensitivity level of college students, and this effect can be positively predicted by warm and supportive interaction behaviors in group sandplay.